Pengaruh Penerapan Bahan Ajar Muatan Lokal Alat-Alat Tradisional Bengkulu Terhadap Sikap Cinta Tanah Air Siswa SDN Kota Bengkulu - Ajeng Permata Sari; Sri Ken Kustianti; Feri Noperman (Universitas Bengkulu, 2018)
This research aimed to determine the effect of the application of local content teaching materials Bengkulu traditional to the love attitude of the homeland of fourth graders in SDN 27 Kota Bengkulu. This type of research is quantitative and the design used in this research was Quasi Experimental with this type of design The Matching Only pretest-posttest control group design, whereas the test twice: before and after giving treatment on a sample class. Subjects in this research are the fourth graders of SDN 27 Kota Bengkulu 2016/2017 academic year consisting of class IVA as experimental class and class IVB as a control class. The research instrument uses a Likert-scale questionnaire. Data of this research are analyzed by using inferential analysis that is t-test. The results show t-test results with t calculate equal to 3.69 and t table value of 2.00. So with the tcalculate (3.69)> t table (2.00). tcalculate that is greater than t table it can be concluded that there are significant implementation of the local content teaching materials traditional tools Bengkulu to the attitude of love for the homeland in the fourth grade students at SDN 27 Kota Bengkulu.